NURTURING STUDENT ENGAGEMENT AND PERSONAL ACHIEVEMENT THROUGH GOAL SETTING: A STRATEGY EVALUATION OF THE ABOUT2BE PROGRAM FOR PROBATIONARY COLLEGE STUDENTS - James, Morgan Branch (East Carolina University, 2019)
This research was a part of a series of studies designed to evaluate the impact of a goal setting strategy entitled About2Be on the engagement and goal setting for probationary college students in the second semester of their freshman year. A quasi-experimental research design was administered utilizing qualitative and quantitative data to evaluate and measure the effectiveness of this intervention. The About2Be Program is designed to encourage students to examine their future and think about goals that are important to them in three categories: career, personal, and academic. The program's structure and activities help students recognize that strengths and areas of challenge are part of everyone's life, and how people plan and reflect on their goals during development can increase success. Additionally, the project sought a strategy that could be taught in such a way that would effectively engage students (e.g., depict information using multiple means of representation). Study participants included freshmen students deemed probationary based on their grade point average (GPA) after their first semester of college during the fall of 2017 (according to the university's GPA policies for good academic standing). Study data included rubric scores from pre and post mission statements, observation data, questionnaires, and usability surveys. No statistically significant differences were found from quantitative analysis between rubric scores on participants' pre and post mission statements. However, themes gathered through qualitative analysis of those mission statements, student feedback surveys and focus groups, and teacher observation data provided valuable information to inform future revisions to the curriculum and future evaluation studies setting resources.
Keywords: Probationary College Students; Goal Setting Strategy; Motivation in education; College students; Education, Higher--Aims and objectives; Academic achievement